Associations of TLR gene polymorphism with the risk of rheumatic heart disease - A. V. Sinitskaya; M. V. Khutornaya; O. N. Khryachkova; A. O. Poddubnyak; M. Yu. Sinitsky; M. A. Asanov; A. V. Ponasenko (Сибирский научный медицинский журнал, 2024)
Aim of the study was to investigate the associations between TLR gene polymorphism and the risk of rheumatic heart disease (RHD).Material and methods. 251 RHD patients (190 females and 61 males) and 300 healthy donors (190 females and 110 males), whose age was 57 [29; 77] and 53 [21; 80] years (median [lower quartile; upper quartile]), respectively, were recruited in the presented study. Eight polymorphic variants in the TLR gene were genotyped by realtime PCR.Results. We found no statistically significant differences in the frequency of eight polymorphic variants in the TLR1, TLR2, TLR4 and TLR6 genes in the general group of patients. Stratification by gender and age showed that the frequency of the C/C genotype of the TLR1 gene (rs5743551) was increased in females with RHD (11.6 %) compared to the control group (5.3 %); a risk effect was determined for recessive inheritance patterns (odds ratio 2.43, 95 % confidence interval 1.07–5.52, p = 0.029). Moreover, the combination of polymorphic variants TLR2 (rs5743708) – TLR4 (rs4689791) – TLR1 (rs5743551) – TLR2 (rs3804099) showed the greatest significance in RHD risk.Conclusions. Future research on the different populations will allow to discover the general patterns of RHD pathogenesis, which will finally lead to the establishment of therapeutic targets for treatment of streptococcal infection and RHD prevention.